Low-dose Intravenous Dexmedetomidine Reduces Shivering Following Cesarean Delivery: A Randomized Controlled Trial. Issue 4 (22nd December 2021) - Sween, L.K.; Xu, S.; Li, C.; O'Donoghue, M.A.; Ciampa, E.J.; Kowalczyk, J.J.; Li, Y.; Hess, P.E.
Abstract : ( Int J Obstet Anesth . 2021;45:49–55) In cesarean deliveries (CD) shivering is sometimes brought on by neuraxial anesthesia. Shivering can negatively affect patient comfort and intraoperative monitoring of blood pressure, electrocardiogram and pulse. Meperidine is a synthetic opioid that has been used to treat postanesthetic shivering, but there are concerns about its side effects in pregnant women. Dexmedetomidine at a dose of 30 μg has been found to control shivering after CD, but with some unpleasant side effects like dry mouth. This study aimed to determine whether anesthetic shivering after CD would be reduced using a 10 μg dose of dexmedetomidine administered immediately after delivery.